2004
DOI: 10.1590/s0037-86822004000700007
|View full text |Cite
|
Sign up to set email alerts
|

Infecções pelos vírus das hepatites B e C e o carcinoma hepatocelular na Amazônia oriental

Abstract: In order to contribute to a better understanding of the possible role of hepatits B and C in the etiopathogenis of HCC in the East Amazon, there were studied 36 patients in Belém/PA. Serological hepatitis markers were evaluated and polymerase chain reaction assays were used to detect HBV-DNA and HCV-RNA. Alcohol abuse was observed in 33.3% and cirrhosis in 83.3%. In 88.9% of the sample, one or more hepatitis B markers were positive. Also, 8.3% those patients had anti-HCV simultaneously positive. The HBsAg sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
2
0
3
Order By: Relevance
“…All patients had a chronic HCV infection. The characterization of chronic infection comprised the detection of seropositivity by means of an ELISA using anti-HCV antibodies, detection of RNA-HCV by PCR, and determination of viral load by quantitative real time PCR (Miranda et al , 2004) Besides serological and molecular detection of HCV, all patients had chronic hepatitis diagnosed according to clinical and histopathologic criteria, as well as laboratorial evaluation of liver function. Co-infection with hepatitis B virus and/or HIV, and association with metabolic or autoimmune disorders were used as exclusion criteria in this study.…”
Section: Methodsmentioning
confidence: 99%
“…All patients had a chronic HCV infection. The characterization of chronic infection comprised the detection of seropositivity by means of an ELISA using anti-HCV antibodies, detection of RNA-HCV by PCR, and determination of viral load by quantitative real time PCR (Miranda et al , 2004) Besides serological and molecular detection of HCV, all patients had chronic hepatitis diagnosed according to clinical and histopathologic criteria, as well as laboratorial evaluation of liver function. Co-infection with hepatitis B virus and/or HIV, and association with metabolic or autoimmune disorders were used as exclusion criteria in this study.…”
Section: Methodsmentioning
confidence: 99%
“…A infecção pelo VHC apresenta alta taxa de progressão para doença crônica ou cirrose subseqüente, excedendo 50% dos casos (8,10,11). O ARN viral é detectável no sangue por 1 a 3 semanas, coincidindo com as elevações das transaminases séricas, e persiste em muitos pacientes a despeito da presença de anticorpos neutralizantes.…”
Section: Como Citarunclassified
“…Muitos estudos soroepidemiológi-cos têm demonstrado o caráter endê-mico de diferentes doenças infecciosas em populações indígenas brasileiras (4,10,(13)(14)(15)(16). Contudo, a grande maioria desses estudos se concentra em populações indígenas da Região Amazônica, onde é relatada uma alta prevalência de infecção pelo VHB.…”
Section: Como Citarunclassified
“…The persistence of HBs and HBe antigens in blood circulation, antibodies against HBV core antigen (anti-HBc), and sometimes antibodies against HBs (anti-HBs) in addition to viral DNA indicates HBV chronic replication, which may be followed by progressive liver injury. A study on the prevalence of serum HBV in Brazil demonstrated that it is endemic in northern regions of the Amazonas as well as in areas of the city of Espírito Santo and the southern States of Paraná and Santa Catarina (Miranda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%